Doped oxide target material for solar cell, preparation method of doped oxide target material and film preparation method

A doped oxide target material for solar cells, using indium oxide with specific element combinations, addresses carrier transport inefficiencies, achieving high mobility and concentration for improved solar cell efficiency and transmittance.

CN119241212APending Publication Date: 2025-01-03WUHU YINGRI TECH CO LTD

Patent Information

Application Number
CN202411316961.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Existing solar cell materials face limitations in carrier transport, leading to inefficiencies in energy conversion due to high series resistance and neglect of carrier concentration, and rely on scarce or toxic materials, hindering mass production and overall efficiency improvement.

Method used

A doped oxide target material for solar cells is prepared using indium oxide with specific doping ratios of wide bandgap, high-valent, and rare earth elements, combined through a multi-step process to achieve high carrier concentration and mobility, ensuring stable production.

Benefits of technology

The solution results in a high-density target material producing a metal oxide film with improved carrier mobility and concentration, enhancing the efficiency and transmittance of solar cell window layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005052480420000071
    Figure BDA0005052480420000071
  • Figure BDA0005052480420000081
    Figure BDA0005052480420000081
  • Figure BDA0005052480420000101
    Figure BDA0005052480420000101
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, and provides a doped oxide target material for a solar cell, which is prepared by simultaneously carrying out composite doping with high-purity indium oxide according to different proportions by using one or two of wide-band gap elements of Ti, Zn, A < l > and Ga, one or two of high-valence metal elements of Ta, Mn, Zr, W and Mo, and one or two of rare earth elements of La, Nd, Sm, Ce, Pr and Y. On the basis of obtaining a high-density target material, a PVD thin film preparation process is optimized, and a metal oxide thin film with high mobility and high carrier concentration for a solar cell window layer is obtained. Through composite doping of wide-band-gap elements, high-valence elements and rare earth elements in a specific proportion and through the comprehensive effect of different types of doped elements, the carrier concentration is synchronously improved on the basis of improving the mobility of the thin film, and the transmittance is not negatively influenced while the carrier concentration is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cell technology, and in particular to a doped oxide target material for solar cells, a preparation method thereof, and a thin film preparation method. Background Art

[0002] With the urgent global demand for clean energy and strong calls for sustainable development, the development and utilization of solar energy, as an inexhaustible energy source, has become increasingly important. As a key device for converting solar energy into electrical energy, the performance improvement and cost reduction of solar cells have always been the focus of scientific research and industry.

[0003] In the development of solar cells, material selection and optimization has always been one of the core issues. Traditional solar cell materials have certain limitations in carrier transport, which makes it difficult to significantly improve energy conversion efficiency. High-mobility targets have excellent carrier transport properties, which can effectively reduce the loss of charge during transmission, increase the short-circuit current and fill factor of the battery, and thus significantly improve the photoelectric conversion efficiency of solar cells.

[0004] At present, many studies have been carried out to explore this, and some results have been achieved, among which: the existing technology patent CN117486584A-a ceramic target material and its preparation method and application-uses indium oxide as the main oxide, with a doping concentration of 98-99.5%, and cerium oxide, scandium oxide, holmium oxide, tantalum oxide, titanium oxide and gallium oxide as doped oxides, with a doped oxide of 0.5-2%, and finally obtains the target material relative density of up to 99.2%, and the film has a maximum carrier mobility of 84.55cm2 / V·s. However, the patent first uses scandium oxide, a scarce resource that is controlled, which is not conducive to the stable and healthy development of the industry. The other oxide used in the patent-holmium oxide is a toxic oxide that may cause respiratory irritation, coughing, and difficulty breathing. The use of these two raw materials will bring limitations to the mass production of the product. Secondly, the patent only expresses concern about the carrier mobility of the film, ignoring the key indicator of carrier concentration. As we all know, whether in the display industry or in the solar cell industry, single-film data can only express part of the application information, and the interface effect also needs to be paid attention to. The carrier concentration will play an important role in the interface effect - determining the size of the series resistance. Too low a carrier concentration will cause the device series resistance to be too high, so even if the single-mode carrier mobility is high, it will not be able to achieve the effect of improving the overall efficiency of the device.

[0005] Coincidentally, CN118026646A-A high-density and high-mobility indium oxide doped target and its preparation method, the patent proposes to use the corresponding components (90-98 parts of indium oxide, 5-8 parts of tin oxide, 1-3 parts of rare earth oxide (lanthanum oxide, praseodymium oxide, neodymium oxide, yttrium oxide), 0.5-1.5 parts of binder, 0.5-0.8 parts of dispersant, 0.3-0.5 parts of stabilizer) to achieve higher density and mobility-relative density 99.57%, target mobility-39.50cm2 / V·s. In this patent, firstly, it only considers the doping of limited rare earth elements, and does not consider the influence of wide bandgap elements (Zn, Al, etc.), high-valent elements (Zr, W, etc.), and other lanthanide elements on mobility. Secondly, from the target to the film, it involves the influence of physical form, crystal structure, grain size, surface state and other aspects. Only expressing the mobility data of the target cannot provide a good guide for its application.

[0006] Therefore, a high-density target material is needed to obtain a metal oxide film with high mobility and high carrier concentration. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a doped oxide target material for solar cells, a preparation method and a thin film preparation method to solve the problems arising in the background technology.

[0008] Based on the above purpose, the present invention provides a doped oxide target for solar cells, wherein the target is prepared from the following raw materials in percentage by mass:

[0009] Indium oxide powder: 95.5-99.7wt%; wide bandgap metal elements are doped in the form of oxide powders, and the doping ratio is 0.1-2wt%, and the wide bandgap metal elements are one or two of Ti, Zn, Al, and Ga; high-valent metal elements are doped in the form of oxide powders, and the doping ratio is 0.1-1.5wt%, and the high-valent elements are one or two of Ta, Mn, Zr, W, and Mo; rare earth elements are doped in the form of oxide powders, and the doping ratio is 0.1-1wt%, and the rare earth elements are one or two of La, Nd, Sm, Ce, Pr, and Y.

[0010] Preferably, the mass percentage of the indium oxide powder is: 98-99.7wt%; the doping ratio of the wide bandgap metal element oxide powder is: 0.1-1wt%; the doping ratio of the high-valent metal element oxide powder is: 0.1-1wt%; and the doping ratio of the rare earth element oxide powder is: 0.1-1wt%.

[0011] The present invention also provides a method for preparing the above-mentioned doped oxide target for solar cells, comprising the following steps:

[0012] Step 1: sand milling the wide bandgap metal element oxide powder, high-valent metal element oxide powder and rare earth element oxide powder to be doped, and finally obtaining slurry 1 with a particle size distribution of D50≤0.25-0.5 μm;

[0013] Step 2, gradually adding indium oxide powder to slurry 1 for ball milling, and finally obtaining slurry 2 with a particle size distribution of D50≤0.25-0.5 μm;

[0014] Step 3, placing the slurry 2 in a centrifugal spray granulator for dryer granulation to obtain a dry and uniformly mixed composite doped metal oxide powder, wherein the obtained powder particle size D50 is ≤25-50 μm and the bulk density is ≥1.4 g / cm3;

[0015] Step 4, placing the granulated composite doped metal oxide powder into a corresponding mold for molding to obtain a green blank;

[0016] Step five, placing the green blank into a sintering furnace and sintering it at high temperature in an oxygen environment to form a tight bond between the powder particles, thereby obtaining a composite doped oxide target having high density, low nodulation, high film yield, high carrier concentration and carrier mobility.

[0017] Preferably, the specific surface area of ​​the doped powder in step 1 is 7-12 m2 / g, the diameter of the zirconium beads used in the sand mill is 0.5-2 mm, the stirring speed is 700-1000 rpm, the stirring time is 1-30 h, the stirring medium is pure water, and the amount of water added: the amount of powder added = 1:1±0.5%,

[0018] Preferably, in the ball milling process of step 2, the amount of water added: the amount of powder added is maintained at 1:1±0.5%, wherein the specific surface area of ​​indium oxide is 5-10㎡ / g, the diameter of the zirconium beads used in the ball mill is 0.5-2mm, the stirring speed is 700-1000 rpm, and the stirring time is 1-30h.

[0019] Preferably, the air inlet temperature of the centrifugal spray granulator in step 3 is 200-230°C, and the air outlet temperature is 80-110°C.

[0020] Preferably, the molding pressure in step 4 is 280-350 MPa, and the molding time is 40-60 minutes.

[0021] Preferably, the sintering temperature and holding time in step 5 are:

[0022] The first stage - dehydration: the temperature is room temperature - 300 ° C, the heating rate is 0.3-3 ° C / min, the insulation time is 0.2-0.5h, no gas protection or nitrogen protection;

[0023] The second stage - sintering and debinding: the temperature is 300-600℃ from room temperature, the heating rate is 0.3-3℃ / min, the holding time is 0.2-0.5h, without gas protection or with nitrogen protection;

[0024] The third stage - sintering: the temperature is 600-800~1300℃ at room temperature, the heating rate is 4-8℃ / min, the holding time is 1-2h, and oxygen protection is used;

[0025] The fourth stage - sintering: the temperature is 800-1300-1400-1600℃ at room temperature, the heating rate is 0.3-3℃ / min, the holding time is 4-40h, and oxygen protection is used;

[0026] The fifth stage - cooling: the temperature is 1400~1600-room temperature ℃, the heating rate is 5-40℃ / min, the insulation time is 4-40h, no gas protection or nitrogen protection.

[0027] The present invention also provides a method for preparing a thin film of a doped oxide target for a solar cell, comprising the following steps:

[0028] The first step is to use a vacuum coating machine with a base vacuum of 2*10 -4 Pa~9*10 -4 Pa;

[0029] Step 2: Pre-plating will be performed before coating. The pre-plating parameters are as follows: power density is 1-3W / cm 2 , the substrate temperature is room temperature-250°C, the controlled pressure is 0.25-1Pa, the argon-oxygen ratio is 1000:1-100:5, the hydrogen concentration is 0.1-2%, and the pre-deposition time is 5-30min;

[0030] Step 3: After the pre-coating is completed, open the sample baffle for coating. The parameters are as follows: power density is 1-3W / cm 2 , the substrate temperature is -250°C at room temperature, the pressure is controlled at 0.25-1Pa, the argon-oxygen ratio is 1000:1 to 100:5, and the hydrogen concentration is 0.1 to 2%;

[0031] Step 4: Anneal the film after coating: the annealing temperature is 150-300°C; and the annealing time is 5-60min.

[0032] Preferably, the background vacuum degree in the first step is 2.5*10-4Pa to 5*10-4Pa;

[0033] The second step pre-plating time is 10-15min;

[0034] The power density of the third step is 1.2-2W / cm2, the substrate temperature is 50-200°C, the controlled pressure is 0.6-0.9Pa; the argon-oxygen ratio is 100:1-100:3, and the hydrogen concentration is 0.3-1%;

[0035] The fourth step: the annealing temperature is 160-210° C., and the annealing time is 5-20 min.

[0036] Beneficial effects of the present invention: The present invention optimizes the PVD film preparation process on the basis of obtaining a high-density target material by using one or two of wide-bandgap elements Ti, Zn, Al, and Ga, one or two of high-valent metal elements Ta, Mn, Zr, W, and Mo, and one or two of rare earth elements La, Nd, Sm, Ce, Pr, and Y to simultaneously perform composite doping with high-purity indium oxide in different proportions, thereby obtaining a metal oxide film with high mobility and high carrier concentration for a solar cell window layer.

[0037] The wide bandgap metal element selected in the present invention has excellent electrical properties and outstanding optical properties, which is beneficial to improving the transmittance of the window layer film, thereby further improving the efficiency of the battery assembly.

[0038] The high valence in the high-valent metal element selected in the present invention refers to a higher valence state than that of indium in indium oxide. The significance lies in that when the high-valent element replaces the indium atoms in the indium oxide lattice during the doping process, more electrons will be released into the conduction band because of its excess valence electrons over indium atoms, which will increase the overall carrier concentration of the material. At the same time, the doping of high-valent elements may also change the band structure of the semiconductor, such as changing the position and width of the valence band and conduction band, etc. These changes will affect the excitation and transition of carriers, thereby also affecting the carrier mobility.

[0039] The rare earth elements selected in the present invention can play a regulating role in multi-element composite doping due to their special variable valence effect, and can also introduce additional electrons or holes as carriers to improve the crystal structure of the material, reduce resistance, and improve conductivity.

[0040] The present invention performs composite doping of wide bandgap elements, high-valent elements, and rare earth elements in specific proportions, and through the combined effects of different types of doping elements, the carrier concentration is simultaneously increased on the basis of improving the film mobility. In addition, due to the introduction of wide bandgap metal elements, the carrier concentration can be increased without causing a negative impact on the transmittance. DETAILED DESCRIPTION

[0041] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0042] It should be noted that, unless otherwise defined, the technical terms or scientific terms used in the present invention should be understood by people with ordinary skills in the field to which the present invention belongs. The "first", "second" and similar words used in the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. "Include" or "comprise" and similar words mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. "Connect" or "connected" and similar words are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right" and the like are only used to indicate relative positional relationships. When the absolute position of the described object changes, the relative positional relationship may also change accordingly.

[0043] The powder ratios of each embodiment are as follows:

[0044] Table 1, specific formulations of Examples 1-5

[0045]

[0046] The preparation methods of the target materials and films of Examples 1-5 are as follows

[0047] Example 1

[0048] The target material preparation method is as follows:

[0049] Step 1: Use a sand mill to sand grind the powder to be doped, wherein the specific surface area of ​​the powder to be doped is 7㎡ / g, the diameter of the zirconium beads used in the sand mill is 0.5mm, the stirring speed is 700 rpm, the stirring time is 1h, the stirring medium is pure water, the amount of water added: the amount of powder added = 1:1 (±0.5%), and finally obtain a slurry 1 with a certain particle size distribution D50≤0.25-0.5μm;

[0050] Step 2: gradually add indium oxide powder to slurry 1 for ball milling, and keep the amount of water added: the amount of powder added = 1:1 (±0.5%), wherein the specific surface of indium oxide is 5㎡ / g, the diameter of the zirconium beads used in the ball mill is 0.5mm, the stirring speed is 700 rpm, the stirring time is 1h, and finally obtain slurry 2 with a certain particle size distribution D50≤0.25-0.5μm;

[0051] Step 2: Place the slurry 2 in a centrifugal spray granulator for dryer granulation, set the air inlet temperature to 200°C and the air outlet temperature to 80°C to obtain a dry and uniformly mixed composite doped metal oxide powder. This process requires the obtained powder particle size D50 to be controlled to be ≤25-50μm and the bulk density to be ≥1.4g / cm 3 ;

[0052] Step 4: Put the granulated composite doped metal oxide powder into a corresponding mold for molding, the molding pressure is 280 MPa, the molding time is 40 minutes, and a green blank of corresponding size is obtained;

[0053] Step 5: Place the green blank into a sintering furnace and sinter at high temperature in an oxygen environment with a certain pressure to form a close bond between the powder particles, and obtain a composite doped oxide target with high density, low nodulation, high film yield, high carrier concentration and carrier mobility. The sintering temperature and holding time are as follows:

[0054]

[0055] The film preparation method is as follows:

[0056] Step 1: To ensure the performance of the film, use a background vacuum of 2*10-4Pa;

[0057] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 1W / cm 2 ; Substrate temperature room temperature; Control pressure: 0.25Pa; Argon oxygen ratio: 1000:1; Hydrogen concentration: 0.1%; Pre-deposition time: 5min

[0058] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 1W / cm 2 ; Substrate temperature: room temperature; Control pressure: 0.25Pa; Argon oxygen ratio: 1000:1; Hydrogen concentration: 0.1%;

[0059] Step 4: After coating, the film is annealed. The annealing process is as follows: annealing temperature: 210; annealing time: 5min.

[0060] Example 2

[0061] Step 1: Use a sand mill to sand grind the powder to be doped, wherein the specific surface area of ​​the powder to be doped is 8㎡ / g, the diameter of the zirconium beads used in the sand mill is 0.7mm, the stirring speed is 800 rpm, the stirring time is 4h, the stirring medium is pure water, the amount of water added: the amount of powder added = 1:1 (±0.5%), and finally obtain a slurry with a certain particle size distribution D50≤0.25-0.5μm;

[0062] Step 2: gradually add indium oxide powder to slurry 1 for ball milling, and keep the amount of water added: the amount of powder added = 1:1 (±0.5%), wherein the specific surface of indium oxide is 6㎡ / g, the diameter of the zirconium beads used in the ball mill is 0.7mm, the stirring speed is 800 rpm, the stirring time is 4h, and finally obtain slurry 2 with a certain particle size distribution D50≤0.25-0.5μm;

[0063] Step 3: Place the slurry 2 in a centrifugal spray granulator for dryer granulation, set the air inlet temperature to 215°C and the air outlet temperature to 90°C to obtain a dry and uniformly mixed composite doped metal oxide powder. This process requires the obtained powder particle size D50 to be ≤25-50μm and the bulk density to be ≥1.4g / cm 3 ;

[0064] Step 4: Put the granulated composite doped metal oxide powder into a corresponding mold for molding, with a molding pressure of 300 MPa and a molding time of 50 minutes to obtain a green blank of corresponding size;

[0065] Step 5: Place the green blank into a sintering furnace and sinter at high temperature in an oxygen environment with a certain pressure to form a close bond between the powder particles, and obtain a composite doped oxide target with high density, low nodulation, high film yield, high carrier concentration and carrier mobility. The sintering temperature and holding time are as follows:

[0066]

[0067] The film preparation method is as follows:

[0068] Step 1: To ensure the performance of the film, use a background vacuum of 2.5*10 -4 Pa;

[0069] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 1.5W / cm 2 ; Substrate temperature: room temperature -250°C; controlled pressure: 0.4Pa; argon-oxygen ratio: 1000:3; hydrogen concentration: 0.3%; pre-deposition time: 10min.

[0070] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 1.2W / cm 2 ; Substrate temperature 100°C; Control pressure: 0.61Pa; Argon oxygen ratio: 1000:5; Hydrogen concentration: 0.3%;

[0071] Step 4: After coating, the film is annealed. The annealing process is as follows: annealing temperature: 210°C; annealing time: 10 min.

[0072] Example 3

[0073] Step 1: Use a sand mill to sand grind the powder to be doped, wherein the specific gravity of the powder to be doped is 7-12 m2 / g, the diameter of the zirconium beads used in the sand mill is 1.5 mm, the stirring speed is 850 rpm, the stirring time is 15 h, the stirring medium is pure water, the amount of water added: the amount of powder added = 1:1 (±0.5%), and finally obtain a slurry 1 with a certain particle size distribution D50≤0.25-0.5 μm;

[0074] Step 2: gradually add indium oxide powder to slurry 1 for ball milling, and keep the amount of water added: the amount of powder added = 1:1 (±0.5%), wherein the specific surface of indium oxide is 7㎡ / g, the diameter of the zirconium beads used in the ball mill is 0.8mm, the stirring speed is 700-1000 rpm, the stirring time is 21h, and finally obtain slurry 2 with a certain particle size distribution D50≤0.25-0.5μm;

[0075] Step 3: Place the slurry 2 in a centrifugal spray granulator for dryer granulation, set the air inlet temperature to 220°C and the air outlet temperature to 101°C, and obtain a dry and uniformly mixed composite doped metal oxide powder. This process requires the obtained powder particle size D50 to be ≤25-50μm and the bulk density to be ≥1.4g / cm 3 ;

[0076] Step 4: Put the granulated composite doped metal oxide powder into a corresponding mold for molding, the molding pressure is 301 MPa, the molding time is 45 minutes, and a green blank of corresponding size is obtained;

[0077] Step 5: Place the green blank into a sintering furnace and sinter at high temperature in an oxygen environment with a certain pressure to form a close bond between the powder particles, and obtain a composite doped oxide target with high density, low nodulation, high film yield, high carrier concentration and carrier mobility. The sintering temperature and holding time are as follows:

[0078]

[0079]

[0080] The film preparation method is as follows:

[0081] Step 1: To ensure the performance of the film, use a background vacuum of 5*10 -4 Pa;

[0082] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 2W / cm 2 ; Substrate temperature 130℃; Control pressure: 0.8Pa; Argon oxygen ratio: 100:2; Hydrogen concentration: 0.5%; Pre-deposition time: 20min.

[0083] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 2W / cm 2 ; Substrate temperature 130°C; Control pressure: 0.9Pa; Argon oxygen ratio: 100:2; Hydrogen concentration: 1%;

[0084] Step 4: After coating, the film is annealed. The annealing process is as follows: annealing temperature: 210°C; annealing time: 30 minutes.

[0085] Example 4

[0086] Step 1: Use a sand mill to sand grind the powder to be doped, wherein the specific surface area of ​​the powder to be doped is 7-12㎡ / g, the diameter of the zirconium beads used in the sand mill is 1.5mm, the stirring speed is 900 rpm, the stirring time is 22h, the stirring medium is pure water, the amount of water added: the amount of powder added = 1:1 (±0.5%), and finally obtain a slurry 1 with a certain particle size distribution D50≤0.25-0.5μm;

[0087] Step 2: gradually add indium oxide powder to slurry 1 for ball milling, and keep the amount of water added: the amount of powder added = 1:1 (±0.5%), wherein the specific surface area of ​​indium oxide is 9㎡ / g, the diameter of the zirconium beads used in the ball mill is 1.5mm, the stirring speed is 900 rpm, the stirring time is 25h, and finally obtain slurry 2 with a certain particle size distribution D50≤0.25-0.5μm;

[0088] Step 3: Place the slurry 2 in a centrifugal spray granulator for dryer granulation, set the air inlet temperature to 220°C and the air outlet temperature to 105°C, and obtain a dry and uniformly mixed composite doped metal oxide powder. This process requires the obtained powder particle size D50 to be ≤25-50μm and the bulk density to be ≥1.4g / cm 3 ;

[0089] Step 4: Put the granulated composite doped metal oxide powder into a corresponding mold for molding, with a molding pressure of 320 MPa and a molding time of 55 minutes to obtain a green blank of corresponding size;

[0090] Step 5: Place the green blank into a sintering furnace and sinter at high temperature in an oxygen environment with a certain pressure to form a close bond between the powder particles, and obtain a composite doped oxide target with high density, low nodulation, high film yield, high carrier concentration and carrier mobility. The sintering temperature and holding time are as follows:

[0091]

[0092]

[0093] The film preparation method is as follows:

[0094] Step 1: To ensure the performance of the film, use a background vacuum of 5*10 -4 Pa;

[0095] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 2.5W / cm 2 ; Substrate temperature 200℃; Control pressure: 0.9Pa; Argon oxygen ratio: 100:3; Hydrogen concentration: 1%; Pre-deposition time: 15min

[0096] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 2.5W / cm 2 ; Substrate temperature 200°C; Control pressure: 0.9Pa; Argon oxygen ratio: 100:3; Hydrogen concentration: 1%;;

[0097] Step 4: After coating, the film is annealed. The annealing process is as follows: annealing temperature: 210°C; annealing time: 20min.

[0098] Example 5

[0099] Step 1: Use a sand mill to sand grind the powder to be doped, wherein the specific surface area of ​​the powder to be doped is 12㎡ / g, the diameter of the zirconium beads used in the sand mill is 2mm, the stirring speed is 1000 rpm, the stirring time is 30h, the stirring medium is pure water, the amount of water added: the amount of powder added = 1:1 (±0.5%), and finally obtain a slurry 1 with a certain particle size distribution D50≤0.25-0.5μm;

[0100] Step 2: gradually add indium oxide powder to slurry 1 for ball milling, and keep the amount of water added: the amount of powder added = 1:1 (±0.5%), wherein the specific surface of indium oxide is 10㎡ / g, the diameter of the zirconium beads used in the ball mill is 2mm, the stirring speed is 1000 rpm, and the stirring time is 30h, and finally obtain slurry 2 with a certain particle size distribution D50≤0.25-0.5μm;

[0101] Step 3: Place the slurry 2 in a centrifugal spray granulator for dryer granulation, set the air inlet temperature to 230°C and the air outlet temperature to 110°C to obtain a dry and uniformly mixed composite doped metal oxide powder. This process requires the obtained powder particle size D50 to be ≤25-50μm and the bulk density to be ≥1.4g / cm 3 ;

[0102] Step 4: Put the granulated composite doped metal oxide powder into a corresponding mold for molding, with a molding pressure of 350 MPa and a molding time of 60 minutes to obtain a green blank of corresponding size;

[0103] Step 5: Place the green blank into a sintering furnace and sinter at high temperature in an oxygen environment with a certain pressure to form a close bond between the powder particles, and obtain a composite doped oxide target with high density, low nodulation, high film yield, high carrier concentration and carrier mobility. The sintering temperature and holding time are as follows:

[0104]

[0105] The film preparation method is as follows:

[0106] Step 1: To ensure the performance of the film, use a background vacuum of 9*10-4Pa;

[0107] Step 2: To further improve the performance of the film, pre-plating will be performed before formal coating. The pre-plating parameters are as follows: power density 3W / cm2; substrate temperature room temperature -250℃; controlled pressure: 1Pa; argon oxygen ratio: 100:5; hydrogen concentration: 2%; pre-plating time: 30min

[0108] Step 3: After the pre-coating is completed, open the sample baffle for formal coating. The parameters are as follows: power density 3W / cm2; substrate temperature 250℃; controlled pressure: 1Pa; argon-oxygen ratio: 100:5; hydrogen concentration: 2%;

[0109] Step 4: After coating, the film is annealed. The annealing process is as follows: annealing temperature: 210°C; annealing time: 60min.

[0110] Two comparative examples are used for comparative analysis, namely, comparative examples 1 and 2:

[0111] Comparative Example 1

[0112] Conventional indium tin oxide target with a ratio of indium oxide to tin oxide of 90:10;

[0113] Comparative Example 2

[0114] High mobility indium tin oxide target with an indium oxide to tin oxide ratio of 99:1.

[0115] Test methods:

[0116] In order to further compare the performance differences between the embodiments, in addition to characterizing the intrinsic performance of each target material, the present invention also uses a magnetron sputtering method to verify the coating of each target material. The present invention uses a four-probe resistivity tester to test the resistivity of the target material; uses a drainage method to test the density of the target material; uses a four-needle square resistance meter to test the square resistance of the film; uses a surface profiler to test the thickness of the film; uses an ultraviolet spectrophotometer to test the transmittance of the film; and uses a Hall effect meter to test the carrier concentration and carrier mobility of the film.

[0117] The target intrinsic performance test results are compared as follows:

[0118]

[0119] From the test results of the intrinsic performance of the target material, it can be seen that the performance of the target material prepared by the method according to the present invention is comparable to that of the comparative example project, with a comparable relative density, a smaller grain size, and a smoother warping.

[0120] film The comparison of performance test results such as transmittance and resistivity is as follows:

[0121]

[0122]

[0123] Comparing the data in the above table, after annealing at 210°C, the film performance has been improved to varying degrees, which will bring feasibility to the actual application of the product involved in the present invention. At the same time, it can be seen that with the increase of the content of the doping elements, the carrier concentration of the film shows an upward trend, and the transmittance of the film shows a downward trend. This is due to the introduction of doping elements. The impurity carriers in the crystal structure of the film increase, resulting in a certain degree of scattering effect, thereby reducing the transmittance of the film. Among them, the carrier mobility data is theoretically closely related to the content of indium oxide. The higher the content of indium oxide, the higher the mobility. However, although the indium oxide content achieved in Examples 2, 3, and 4 of the present invention is lower than the traditional 99:1 comparative example 2, its mobility shows a very obvious advantage. This is due to the effect between the doping elements. On the basis of introducing more carriers, the carrier mobility is still improved.

[0124] It should be understood by those skilled in the art that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the present invention is limited to these examples; under the concept of the present invention, the technical features in the above embodiments or different embodiments may also be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity. Any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.

Claims

1. A doped oxide target for solar cells, characterized in that: The target material is prepared from the following raw materials in percentage by mass: Indium oxide powder: 95.5-99.7wt%; wide bandgap metal elements are doped in the form of oxide powders, and the doping ratio is 0.1-2wt%, and the wide bandgap metal elements are one or two of Ti, Zn, Al, and Ga; high-valent metal elements are doped in the form of oxide powders, and the doping ratio is 0.1-1.5wt%, and the high-valent elements are one or two of Ta, Mn, Zr, W, and Mo; rare earth elements are doped in the form of oxide powders, and the doping ratio is 0.1-1wt%, and the rare earth elements are one or two of La, Nd, Sm, Ce, Pr, and Y.

2. The doped oxide target for solar cells according to claim 1, characterized in that: The mass percentage of the indium oxide powder is: 98-99.7wt%; the doping ratio of the wide bandgap metal element oxide powder is: 0.1-1wt%; the doping ratio of the high-valent metal element oxide powder is: 0.1-1wt%; and the doping ratio of the rare earth element oxide powder is: 0.1-1wt%.

3. The method for preparing a doped oxide target for solar cells according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1: sand milling the wide bandgap metal element oxide powder, high-valent metal element oxide powder and rare earth element oxide powder to be doped, and finally obtaining slurry 1 with a particle size distribution of D50≤0.25-0.5 μm; Step 2, gradually adding indium oxide powder to slurry 1 for ball milling, and finally obtaining slurry 2 with a particle size distribution D50≤0.25-0.5 μm; Step 3, placing the slurry 2 in a centrifugal spray granulator for dryer granulation to obtain a dry and uniformly mixed composite doped metal oxide powder, wherein the obtained powder particle size D50 is ≤25-50 μm and the bulk density is ≥1.4 g / cm3; Step 4, placing the granulated composite doped metal oxide powder into a corresponding mold for molding to obtain a green blank; Step five, placing the green blank into a sintering furnace and sintering it at high temperature in an oxygen environment to form a tight bond between the powder particles, thereby obtaining a composite doped oxide target having high density, low nodulation, high film yield, high carrier concentration and carrier mobility.

4. The method for preparing a doped oxide target for solar cells according to claim 3, characterized in that: The specific surface area of ​​the doped powder in step 1 is 7-12 m2 / g, the diameter of the zirconium beads used in the sand mill is 0.5-2 mm, the stirring speed is 700-1000 rpm, the stirring time is 1-30 h, the stirring medium is pure water, and the amount of water added: the amount of powder added = 1:1±0.5%.

5. The method for preparing a doped oxide target for solar cells according to claim 4, characterized in that: In the ball milling process of step 2, the amount of water added: the amount of powder added is maintained at 1:1±0.5%, wherein the specific surface area of ​​indium oxide is 5-10㎡ / g, the diameter of the zirconium beads used in the ball mill is 0.5-2mm, the stirring speed is 700-1000 rpm, and the stirring time is 1-30h.

6. The method for preparing a doped oxide target for solar cells according to claim 5, characterized in that: In step 3, the air inlet temperature of the centrifugal spray granulator is 200-230°C, and the air outlet temperature is 80-110°C.

7. The method for preparing a doped oxide target for solar cells according to claim 6, characterized in that: The molding pressure in step 4 is 280-350 MPa, and the molding time is 40-60 minutes.

8. The method for preparing a doped oxide target for solar cells according to claim 7, characterized in that: The sintering temperature and holding time of step 5 are: The first stage - dehydration: the temperature is room temperature - 300 ° C, the heating rate is 0.3-3 ° C / min, the insulation time is 0.2-0.5h, no gas protection or nitrogen protection; The second stage - sintering and debinding: the temperature is 300-600℃ from room temperature, the heating rate is 0.3-3℃ / min, the holding time is 0.2-0.5h, without gas protection or with nitrogen protection; The third stage - sintering: the temperature is 600-800~1300℃ at room temperature, the heating rate is 4-8℃ / min, the holding time is 1-2h, and oxygen protection is used; The fourth stage - sintering: the temperature is 800-1300-1400-1600℃ at room temperature, the heating rate is 0.3-3℃ / min, the holding time is 4-40h, and oxygen protection is used; The fifth stage - cooling: the temperature is 1400~1600-room temperature ℃, the heating rate is 5-40℃ / min, the insulation time is 4-40h, no gas protection or nitrogen protection.

9. The method for preparing a thin film of a doped oxide target for solar cells according to any one of claims 1 to 2, characterized in that: The following steps are involved: The first step is to use a vacuum coating machine with a base vacuum of 2*10 -4 Pa~9*10 -4 Pa; Step 2: Pre-plating will be performed before coating. The pre-plating parameters are as follows: power density is 1-3W / cm 2 , the substrate temperature is room temperature-250°C, the controlled pressure is 0.25-1Pa, the argon-oxygen ratio is 1000:1-100:5, the hydrogen concentration is 0.1-2%, and the pre-deposition time is 5-30min; Step 3: After the pre-coating is completed, open the sample baffle for coating. The parameters are as follows: power density is 1-3W / cm 2 , the substrate temperature is -250°C at room temperature, the pressure is controlled at 0.25-1Pa, the argon-oxygen ratio is 1000:1 to 100:5, and the hydrogen concentration is 0.1 to 2%; Step 4: Anneal the film after coating: the annealing temperature is 150-300°C; and the annealing time is 5-60min.

10. The method for preparing a thin film of a doped oxide target for solar cells according to claim 9, characterized in that: The background vacuum degree of the first step is 2.5*10-4Pa~5*10-4Pa; The second step pre-plating time is 10-15min; The power density of the third step is 1.2-2W / cm2, the substrate temperature is 50-200°C, the controlled pressure is 0.6-0.9Pa; the argon-oxygen ratio is 100:1-100:3, and the hydrogen concentration is 0.3-1%; The fourth step: the annealing temperature is 160-210° C., and the annealing time is 5-20 min.

Citation Information

Patent Citations

  • A belt clearance width modulating gallium indium oxide film and its making method

    CN101262017A

  • Aluminum indium oxide thin film material with adjustable band gap width and preparation method thereof

    CN103789745A

  • High-mobility indium titanium cerium tantalum oxide target material and preparation method thereof

    CN116639956A

  • High-valence element doped indium tin oxide material as well as preparation method and application thereof

    CN116730710A

  • Conductive film and preparation method thereof

    CN117954148A

Cited By

  • High-mobility IGO target material and preparation method and application thereof

    CN120099456A

  • High mobility igo target material, method of making and use thereof

    CN120099456B